Crystallinity and rheology of HDPE/PA12 blends compatibilized with HDPE‐alt‐MAH - Almeida Santos da Silva, Geovane; d'Almeida, José Roberto Moraes; Letichevsky, Sonia; Avillez, Roberto Ribeiro (Polymers for advanced technologies, 2023)
This work studies the crystallinity and rheology of HDPE/PA12 blends compatibilized with 2 wt% of HDPE‐alt‐MAH. Specimens of HDPE/PA12 blends were extruded and injected into a mold with 75/25, 50/50, and 25/75 HDPE/PA ratios. The Fourier‐transform infrared spectroscopy (FTIR) analysis showed that no oxidation reaction occurred in the high‐temperature processing and that stronger interactions between the components of the blends occurred in the polyamide's functional groups. The x‐ray diffraction (XRD) analysis showed that the crystallinity degree of the blends and the mean crystallite sizes decreased with the addition of PA12 for both blends. The HDPE's lattice parameters were consistent with the values in the literature, whereas for the PA12, it was not possible to fit its lattice parameters. The rheology analysis evaluated the relationship between the shear stress and viscosity and found that the HDPE/PA 75/25 blend was the most pseudoplastic, presenting the best processability under high shear rates.